Pengembangan Buku Ajar Bold Make Up Look Pengantin Wanita Tapanuli Selatan pada Mata Kuliah Tata Rias Pengantin Indonesia Bagian Barat - Erianti, Lisa Rizki; Irtawidjajanti , Sri; Hidayah, Nurul (Innovative: Journal Of Social Science Research, 2025)
This study is a research and development (R&D) project that employs the 4D development model, which consists of Define, Design, Develop, and Disseminate stages. The product developed is a teaching book titled Bold Make Up Look for South Tapanuli Bride, intended as a learning medium for the course "Traditional Indonesian Bridal Make-Up (Western Region)." Data collection was conducted through the distribution of questionnaires to subject matter experts, and the data were analyzed using both qualitative and quantitative approaches. The validation results showed that the teaching book received a score of 94% from the subject matter expert. Based on these results, the teaching book is declared valid with the category "Highly Feasible" for use as a learning medium.